Describe some language structures in 4 years normal children's narrative in Isfahan and its relationship with sex according to Narrative Assessment Protocol (NAP) - Moslem Ghasemi; Mahboubeh Nakhshab; Batoul Alinejac; Meysam Shafiei; Mahdi Tazhibi (Vesnu Publications, 2012)
Introduction: Narrative assessment is an important evaluative tool for determining literacy outcomes, academic performance and social appropriateness. It can be viewed as rich approach for the description of how language develops in early childhood environments. The aim of this study was to report some language structures in narrations produced by 4-year-olds and to explore any association that may be observed between those structures and the sex of these children according to Narrative Assessment Protocol (NAP). Materials and Methods: In this cross-sectional descriptive study, NAP method was used to evaluate particular language structures in spontaneous narrations of 126 Persian-speaking children that had been produce while they were describing a picture book. Intra-rater, inter-rater and online- offline reliabilities were also calculated. Results: Target language structures were evident in the most of narratives. The most commonly used structure was possessive noun and the least common one was tier-two noun. Agreement percentage for each of the NAP items ranged from 53% to 100% of accuracy. The final NAP score for each subject and the scores obtained for each structure were not significantly different between girls and boys. Conclusion: The results were in agreement with the past results about the Mean Length of Utterance (MLU) in various ages and the relationship between MLU and the development of language structures in this age range. Keywords: Narration, Language, Narrative Assessment Protocol, Children